2022
DOI: 10.21203/rs.3.rs-1752713/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of the Electrolyte concentration and amount on the Performance of Textile Electrodes in Electrostimulation: a systematic study

Abstract: Background Textile-based stimulation electrodes are a fast-growing research area. With their advantages including reusability and the possibility for integration into garments, textile electrodes open up new possibilities that are not yet feasible today, e.g. various self-administrated treatments and rehabilitation based on neuromuscular electrical stimulation (NMES) or transcutaneous electrical nerve stimulation (TENS). So far, most research has shown that textile-based stimulation electrodes perform more re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…Throughout the literature, both pure water and sodium chloride solution are commonly used as electrolytes alongside textile electrodes during electrical stimulation [12], [13]. To this end, both the volume and concentration of sodium chloride required for textile electrode function have been previously established [14]. Furthermore, it has been demonstrated that most water-based electrolytes, such as pure water, saline and conductive gel, gradually evaporate, resulting in signal degradation for long-term use [10].…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the literature, both pure water and sodium chloride solution are commonly used as electrolytes alongside textile electrodes during electrical stimulation [12], [13]. To this end, both the volume and concentration of sodium chloride required for textile electrode function have been previously established [14]. Furthermore, it has been demonstrated that most water-based electrolytes, such as pure water, saline and conductive gel, gradually evaporate, resulting in signal degradation for long-term use [10].…”
Section: Introductionmentioning
confidence: 99%